What has become of the audit explosion? Analyzing trends in oversight activities in the Canadian government. (6th November 2021) - Liston‐Heyes, Catherine; Juillet, Luc
Abstract: Since the 1980s, many governments expanded their administrative oversight systems, such as auditing and evaluation, in order to improve the efficiency, performance and accountability of their administration. Yet few studies empirically examine this "audit explosion." Our study investigates its more recent manifestation. Using Canada as an exploratory case, we first assess whether the level of these oversight activities contracted or expanded in the last two decades. We then analyze the contents of 3245 audit reports published between 2000 and 2019 to track changes in the focus of auditing. Results suggest that, while the overall level of administrative oversight is much higher now than in 2000, it grew only in the first decade of the millennium and was confined to internal functions, namely departmental audits and evaluations, as opposed to the country's Supreme Audit Institution. Meanwhile, auditors' attention to financial matters declined, while their focus on compliance, performance, and risk increased. Résumé: Depuis 1980, plusieurs gouvernements ont renforcé leurs systèmes d'audit et d'évaluation afin d'améliorer l'efficience, la performance et l'imputabilité de leur administration. Toutefois, peu d'études examinent empiriquement cette « explosion de la vérification ». Notre étude examine les développements récents dans ce domaine. Utilisant le Canada comme cas exploratoire, nous évaluons d'abord l'évolution du nombre d'audits et d'évaluations au cours des deux dernières décennies. Nous analysons ensuite le contenu de 3245 rapports d'audit pour comprendre comment les préoccupations des vérificateurs ont évolué entre 2000 et 2019. Nos résultats suggèrent que, si le niveau global de vérification et d'évaluation est beaucoup plus élevé aujourd'hui qu'en 2000, cette augmentation fut limitée à la première décennie du millénaire et aux évaluations et audits ministériels par opposition à la vérification législative. Par ailleurs, l'attention portée aux questions financières a diminué, tandis qu'on observe un accent croissant mis sur la conformité, la performance et le risque.